2016
DOI: 10.1161/strokeaha.116.013952
|View full text |Cite|
|
Sign up to set email alerts
|

Remote Intracerebral Hemorrhage After Intravenous Thrombolysis

Abstract: Background and Purpose— Remote parenchymal hemorrhage (rPH) after intravenous thrombolysis with recombinant tissue-type plasminogen activator may be associated with cerebral amyloid angiopathy, although supportive data are limited. We aimed to investigate risk factors of rPH after intravenous thrombolysis with recombinant tissue-type plasminogen activator. Methods— This is an observational study of patients with ischemic stroke who were treated with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…There is increasing evidence of a link between CAA and ICH after IV-rtPA [2,11,12]. A large meta-analysis [11] of patients with ischemic stroke who were treated with IV-rtPA showed that patients who exhibited CMB and had a high burden of CMB were associated with a high risk symptomatic ICH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is increasing evidence of a link between CAA and ICH after IV-rtPA [2,11,12]. A large meta-analysis [11] of patients with ischemic stroke who were treated with IV-rtPA showed that patients who exhibited CMB and had a high burden of CMB were associated with a high risk symptomatic ICH.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies [11,12] a separate analysis of rPH was not reported. Recently, a multicenter study [2] showed that lobar CMB were associated with rPH. In addition, rPH after IV-rtPA has been documented to occur at a site of CMB [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations